2021
DOI: 10.1021/acs.langmuir.1c01821
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Enzymes in Metal–Phenolic Network Capsules for the Trigger of Intracellular Cascade Reactions

Abstract: Nanoengineered capsules encapsulated with functional cargos (e.g., enzymes) are of interest for various applications including catalysis, bioreactions, sensing, and drug delivery. Herein, we report a facile strategy to engineer enzyme-encapsulated metal–phenolic network (MPN) capsules using enzyme-loaded zeolitic imidazolate framework nanoparticles (ZIF-8 NPs) as templates, which can be removed in a mild condition (e.g., ethylenediaminetetraacetic acid (EDTA) solution). The capsule size (from 250 nm to 1 μm) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We can infer the successful synthesis of GOx@MPN capsules by the change in z potential from the positive to negative charge of ZIF-8 NPs (30.4 mV), GOx@ZIF-8 NPs (À8.9 mV), GOx@ZIF-8@MPN NPs (À26.6 mV), and GOx@MPN capsules (À42.3 mV). 60 In addition, most of the literature studies described in this paper have achieved good synthetic results by either compositing Zn-MOFs with other nanomaterials or functionalising them under room temperature synthesis conditions. Liu et al synthesized a clickable ligand (norbornene-modified imidazole (MIM-Nor)) by introducing an imidazole ligand partially into norbornene and embedding it into ZIF-8 during particle formation, which was then attached to the surface of cetuximab (Cet) to obtain Cet@POI@ZIF-8N, providing a way for other targeting ligands to be able to more readily modify the surface of the surface of ZIF-8N.…”
Section: Room Temperature Synthesismentioning
confidence: 89%
“…We can infer the successful synthesis of GOx@MPN capsules by the change in z potential from the positive to negative charge of ZIF-8 NPs (30.4 mV), GOx@ZIF-8 NPs (À8.9 mV), GOx@ZIF-8@MPN NPs (À26.6 mV), and GOx@MPN capsules (À42.3 mV). 60 In addition, most of the literature studies described in this paper have achieved good synthetic results by either compositing Zn-MOFs with other nanomaterials or functionalising them under room temperature synthesis conditions. Liu et al synthesized a clickable ligand (norbornene-modified imidazole (MIM-Nor)) by introducing an imidazole ligand partially into norbornene and embedding it into ZIF-8 during particle formation, which was then attached to the surface of cetuximab (Cet) to obtain Cet@POI@ZIF-8N, providing a way for other targeting ligands to be able to more readily modify the surface of the surface of ZIF-8N.…”
Section: Room Temperature Synthesismentioning
confidence: 89%
“…27 Second, the phenolic moieties can generate diverse interactions with different molecules and substrates 27 including hydrogen bonding (with poly(ethylene glycol) (PEG), as an example), 114 metal coordination (with Fe 3+ ions), 115 π−π interaction (with graphene oxide), 116 and hydrophobic interactions (with aliphatic side chains). 117 Thus, MPNs have been assembled into a range of materials including NPs, 118 capsules, 119 conformal coatings, 120 and freestanding films. 24 Third, the dynamic coordination bonds between the metal ions and phenolic moieties can be broken and restored through various stimuli (e.g., pH and ionic strength), endowing MPN-based materials with tunable permeability, 121 high toughness, 122 and self-healing properties.…”
Section: Materials Formed Via Coordination Interactionsmentioning
confidence: 99%
“…53,54 We have previously reported that the combination of glucose oxidase (GOx) and iron ions into the same carriers could generate ROS via triggering the cascade reactions in the presence of glucose. 55 Herein, mesoporous silica/GOx@ tannic acid/Fe 2+ (MS/GOx@TA/Fe 2+ ) NPs were prepared and used as a microreactor (Fig. S20-S23 †).…”
Section: Mouse Motion Sensing and Cascade Reaction Monitoringmentioning
confidence: 99%